Progress in devulcanization of waste tire rubber: Upcycling towards a circular economy - Zaheer ul Haq; Teng Ren; Xinyan Yue; Krzysztof Formela; Denis Rodrigue; Xavier Colom Fajula; Tony McNally; Dong Dawei; Yong Zhang; Shifeng Wang (eXPRESS Polymer Letters)
As a complex composite material, tire rubber has always presented significant environmental and waste management concerns due to its non-biodegradability and accumulation in landfills. The devulcanization of tire rubber has emerged as a historical challenge in the field of sustainable rubber engineering since Goodyear invented cross-linking in 1839. This review provides a comprehensive analysis of waste tire recycling processes, focusing on the sources, legislation, management strategies, and utilization across different regions. It explores the multifaceted challenges of devulcanizing rubber, with a specific focus on transitioning from ground tire rubber to the concept of multi-decrosslinking: sulfur bridge breakage, rubber chain depolymerization and micro-nano sized core-shell carbon black. Ideal devulcanization has restricted the release of reinforcing fillers, resulting in devulcanized rubber mainly containing dozens of micron particles, which hinder the wide usage of devulcanized rubber. This review comprehensively assesses the current state-of-the-art techniques for tire rubber devulcanization, including physical, chemical and biological methods. It explores the intricacies of ground tire rubber as a starting material, structural evolution of ground tire rubber during the devulcanization process and the associated challenges in achieving efficient devulcanization while retaining desirable mechanical properties. Furthermore, through an in-depth analysis of recent advancements, limitations and prospects, this paper offers a complete understanding of the challenges faced in tire rubber devulcanization. Considering the technical and environmental aspects of these processes, this work contributes to multi-decrosslinking, the ongoing discourse on sustainable materials development and circular economy initiatives, which pave the way for future innovations in the field of rubber recycling.